PENGEMBANGAN MASASE OLAHRAGA UNTUK PEMANASAN BAGI ATLET PUTRI KLUB BOLAVOLI PERKASA JAYA BLITAR - Rohmawati, Sebtian Kristin Anita; surendra, Mulyani; Purnami, Sri (Jurnal Sport Science, 2016)
Abstract :This researchaims to develop asportsmassagetowarm uponthe sportvolleyballas an alternativeform of heatingthat is usefultohelpprepare thephysical conditionbeforetrainingor competing. Expectedresults ofthisdevelopmentis beneficial towomen athletesvolleyballclubPerkasaJayaBlitar. Thisresearchmethodrefers to amodel ofthe development ofresearch anddevelopment(R &D) ofBorgandGallusesquantitative and qualitative analysis. Results ofdevelopmentin the form ofa guide book thentested ona smallgroup oftest phaseinvolving10women athletesvolleyballclubPerkasaJayaBlitarobtaina yield of88% so thatit can be usedanda largegroup trialinvolving 30women athletesvolleyballclubPerkasaJayaBlitarresultby 90,5% so itcanbe used.Key word :sports massage, warming up, volleyball